Conductivity inspection method, peeling method, electrically peelable adhesive layer, and adhesive sheet

By using the conductive inspection method of the electrically peeled adhesive layer and the applied voltage, the efficiency problem of inspection of electronic components in the prior art is solved, and efficient determination of conductive characteristics and easy peeling of residues is achieved.

CN119678054APending Publication Date: 2025-03-21NITTO DENKO CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380056840.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-05
Filing Date
2023-08-04
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, when inspecting a large number of electronic components, it is difficult to efficiently carry out the process of energizing, measuring the current value or resistance value, and distinguishing the unqualified product.

Method used

Using a conductivity inspection method with a specific process, an electrically peeled adhesive layer is used to bond the inspection object to the fixing member, and its conductivity characteristics are determined by applying a voltage.

Benefits of technology

It is possible to efficiently determine the conductivity characteristics of the inspection object, and to easily peel off the inspection object remaining on the electrically peeled adhesive layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119678054A_ABST
    Figure CN119678054A_ABST
Patent Text Reader

Abstract

Conduction characteristics of an object to be inspected are efficiently determined. In the conductive inspection method, an object to be inspected (a conductor 3 or an insulator 4) is joined to a fixing member 2 using an electrically peelable adhesive layer 1 capable of joining the object to be inspected and the fixing member 2, and a voltage is applied to the object to be inspected and the electrically peelable adhesive layer 1. The conductive characteristics of the object to be inspected are determined on the basis of the state of engagement between the object to be inspected and the fixing member 2 after the voltage has been applied.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a conductive inspection method, a stripping method, an electro-stripping adhesive layer and an adhesive sheet. Background Art

[0002] In recent years, with the increasing demand for various electronic components, various electronic component inspection methods have been proposed. For example, in a capacitor inspection method as one type of electronic component, there is a method of measuring the current value or resistance value of each capacitor and determining whether it is qualified or not by comparing it with a threshold value (for example, see Patent Documents 1 and 2).

[0003] In addition, a method for improving the efficiency of inspection by inspecting a plurality of electronic components at once has been proposed (for example, see Patent Document 3). In this method, a plurality of conductive small pieces corresponding to electronic components are fixed with a conductive adhesive, the electrodes of the conductive small pieces are brought into contact with the adhesive, and a current is passed through each conductive small piece via the adhesive. In this way, all the conductive small pieces on the adhesive can be inspected simultaneously and at once.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2018-41821

[0007] Patent Document 2: Japanese Patent Application Publication No. 2018-41822

[0008] Patent Document 3: Japanese Patent Application Publication No. 2020-125436 Summary of the invention

[0009] Problems to be solved by the invention

[0010] For the methods described in Patent Documents 1 and 2, when inspecting a large number of electronic components, it is difficult to efficiently inspect them because it is necessary to energize each electronic component, measure the current value or resistance value, and perform a pass / fail judgment. The method described in Patent Document 3 can simultaneously and efficiently energize a large number of conductive small pieces, but on the other hand, it does not disclose a method for simultaneously and collectively performing a process of measuring the current value or resistance value, and a process of distinguishing defective products by comparing with a threshold value, and cannot provide a solution to the problem that this application is the subject of.

[0011] One object of the present invention is to provide a conductive inspection method capable of efficiently inspecting the conductive properties of an inspection object. Another object of the present invention is to provide a stripping method capable of efficiently inspecting the conductive properties of an inspection object by using an electrically strippable adhesive layer and capable of easily stripping the inspection object remaining on the electrically strippable adhesive layer. In addition, one object of the present invention is to provide an electrically strippable adhesive layer and an adhesive sheet that can be suitably used in the stripping method.

[0012] Means for solving problems

[0013] The inventors of the present application have conducted intensive studies and have found that the above-mentioned problems can be solved by a conductivity inspection method having a specific process.

[0014] That is, the present invention provides a conductive inspection method, wherein an inspection object and a fixing member are joined using an electrically peelable adhesive layer capable of joining the inspection object and the fixing member,

[0015] applying a voltage to the inspection object and the electro-peelable adhesive layer,

[0016] The conductive property of the inspection object is determined based on the bonding state between the inspection object and the fixing member after voltage application.

[0017] In one aspect of the conductivity inspection method of the present invention, whether the inspection object is a conductor or an insulator may be determined based on the conductivity characteristics of the inspection object.

[0018] In one aspect of the conductivity inspection method of the present invention, whether the inspection object is a conforming product or a defective product may be determined based on the conductivity characteristics of the inspection object.

[0019] In one aspect of the conductivity inspection method of the present invention, the inspection object may be classified simultaneously with the determination of the conductivity characteristics of the inspection object.

[0020] In one aspect of the conductivity inspection method of the present invention, the fixing member may have conductivity, and a voltage may be applied to the electrically peelable adhesive layer via the inspection object and the fixing member.

[0021] In one embodiment of the conductivity inspection method of the present invention, the electrically peelable adhesive layer may have a single layer structure, the fixing member may have conductivity, a positive electrode for applying voltage may be connected to the fixing member, and a negative electrode for applying voltage may be connected to the inspection object.

[0022] In one aspect of the conductivity inspection method of the present invention, a voltage may be applied to the electrically peelable adhesive layer via the inspection object and the conductive layer in a state where an adhesive layer and a conductive layer are further disposed between the electrically peelable adhesive layer and the fixing member.

[0023] In one aspect of the conductivity inspection method of the present invention, a positive electrode for applying a voltage may be connected to the conductive layer, and a negative electrode for applying a voltage may be connected to the inspection object.

[0024] In one embodiment of the conductivity inspection method of the present invention, the electrically-debonding adhesive layer may contain an electrolyte.

[0025] In one embodiment of the conductivity inspection method of the present invention, the electro-peelable adhesive layer may contain an ionic liquid.

[0026] In one embodiment of the conductivity testing method of the present invention, the anion of the ionic liquid may be selected from (FSO 2 ) 2 N - ,(CF 3 SO 2 ) 2 N - ,(CF 3 CF 2 SO 2 ) 2 N - ,(CF 3 SO 2 ) 3 C - , CH 3 COO - CF 3 COO - CF 3 CF 2 CF 2 COO - CF 3 SO 3 - CF 3 (CF 2 ) 3 SO 3 - Br - 、AlCl 4 - 、Al 2 Cl 7 - 、NO 3 - , BF 4- PF 6 - , AsF 6 - , SbF 6 - , and F(HF) n - (n represents an integer greater than or equal to 1) at least one anion selected from the group consisting of:

[0027] Furthermore, the inventors of the present application have found that the above-mentioned problems can be solved by a peeling method having an additional step in the above-mentioned conductivity inspection method.

[0028] That is, the present invention provides a stripping method, wherein, in the above-mentioned conductive inspection method,

[0029] After applying voltage to the inspection object and the electro-peelable adhesive layer,

[0030] supplying a predetermined energy or substance other than electricity to the electro-peelable adhesive layer,

[0031] The conductive property of the inspection object is determined, and the remaining inspection object bonded to the electrically peelable adhesive layer after the voltage is applied is peeled off.

[0032] In one aspect of the stripping method of the present invention, the remaining inspection object may be an insulator.

[0033] In one embodiment of the peeling method of the present invention, heat may be supplied to the electropeelable adhesive layer as the predetermined energy.

[0034] In one embodiment of the peeling method of the present invention, active energy rays may be supplied to the electropeelable adhesive layer as the predetermined energy.

[0035] In one embodiment of the stripping method of the present invention, after applying voltage to the inspection object and the electrically strippable adhesive layer, the conductive properties of the inspection object are determined, and then a predetermined energy or substance other than electricity is supplied to the electrically strippable adhesive layer to strip the remaining inspection object.

[0036] Furthermore, the inventors of the present application have proposed the structures of an electro-peelable adhesive layer and an adhesive sheet that can be applied to the above-mentioned peeling method.

[0037] The present invention provides an electro-strippable adhesive layer comprising: a polymer; an electrolyte; and a thermally expandable filler.

[0038] The present invention provides an electro-peelable adhesive layer comprising a polymer and an electrolyte, the electro-peelable adhesive layer being cured by irradiation of active energy rays or by heating.

[0039] The present invention provides an electro-peelable adhesive layer comprising: a polymer; an electrolyte; and at least one compound selected from the group consisting of a surfactant and a compound having a polyoxyalkylene skeleton.

[0040] The present invention provides a pressure-sensitive adhesive sheet comprising any of the above-described electro-release pressure-sensitive adhesive layers.

[0041] Effects of the Invention

[0042] According to one aspect of the present invention, the conductive properties of an inspection object can be determined efficiently. According to another aspect of the present invention, the conductive properties of an inspection object can be determined efficiently, and the inspection object remaining on the electrically strippable adhesive layer can be easily stripped. According to yet another aspect of the present invention, an electrically strippable adhesive layer and an adhesive sheet that can be suitably used in the above stripping method can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] [ Figure 1 ] Figure 1 It is a diagram schematically showing the process of the conductivity inspection method according to the first embodiment of the present invention.

[0044] [ Figure 2 ] Figure 2 This is a schematic diagram for explaining an example of the conductivity inspection method according to the first embodiment of the present invention.

[0045] [ Figure 3 ] Figure 3 This is a schematic diagram for explaining an example of the peeling method according to the first embodiment of the present invention.

[0046] [ Figure 4 ] Figure 4 It is a diagram schematically showing the process of the conductivity inspection method according to the second embodiment of the present invention.

[0047] [ Figure 5 ] Figure 5 This is a cross-sectional view schematically showing the method of the 180° peel test in the example. DETAILED DESCRIPTION

[0048] (First embodiment)

[0049] Hereinafter, specific embodiments of the present invention will be described with reference to the drawings. Figure 1 It is a diagram schematically showing the process of the conductivity inspection method according to the first embodiment of the present invention.

[0050] <Overview of Conductivity Inspection Method>

[0051] like Figure 1 As shown on the left side of FIG. 1 , in the conductivity inspection method of this embodiment, a conductor 3 or an insulator 4 as an inspection object is joined to a fixing member 2 using an electrically peelable adhesive layer 1 capable of joining the inspection object to the fixing member 2. Next, as shown in FIG. Figure 1 As shown on the left side of FIG. 1 , a voltage is applied to the inspection object and the electro-peelable adhesive layer 1 using a predetermined voltage applying device. In this embodiment, a voltage is applied to the electro-peelable adhesive layer 1 via the inspection object and the fixing member. After the voltage is applied, as shown in FIG. Figure 1 As shown on the right side of , the pass or fail of the inspection object is determined based on the bonding state between the inspection object and the fixing member 2. Hereinafter, each component used in the conductivity inspection method will be described.

[0052] <Electro-peelable Adhesive Layer>

[0053] The electro-peelable adhesive layer 1 is an adhesive layer obtained from an electro-peelable adhesive (electro-peelable adhesive layer), and contains a polymer as an adhesive and an electrolyte. The electro-peelable adhesive layer 1 has its adhesive strength to an adherend reduced by application of a voltage.

[0054] Examples of the polymer contained in the electro-peelable adhesive layer 1 include acrylic polymers, rubber polymers, vinyl alkyl ether polymers, silicone polymers, polyester polymers, polyamide polymers, urethane polymers, fluorine polymers, and epoxy polymers. The electro-peelable adhesive layer 1 may contain only one type of polymer or two or more types of polymers.

[0055] From the viewpoint of reducing costs and achieving high productivity, it is preferred to contain an acrylic acid polymer. An acrylic acid polymer refers to a polymer containing a monomer unit derived from an alkyl acrylate and / or an alkyl methacrylate as the main monomer unit with the largest mass ratio. Hereinafter, "(meth)acrylic acid" refers to "acrylic acid" and / or "methacrylic acid".

[0056] When the electro-peelable adhesive layer 1 contains an acrylic polymer, the acrylic polymer preferably contains a monomer unit derived from an alkyl (meth)acrylate having an alkyl group with 1 to 14 carbon atoms. Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, 1,3-dimethylbutyl acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylbutyl (meth)acrylate, heptyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate, n-tridecyl (meth)acrylate, and n-tetradecyl (meth)acrylate. Among the above, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate and isononyl (meth)acrylate are preferred. In addition, one alkyl (meth)acrylate may be used, or two or more alkyl (meth)acrylates may be used.

[0057] The ratio of the monomer unit derived from the (meth)acrylic acid alkyl ester having an alkyl group with 1 to 14 carbon atoms in the acrylic polymer is preferably 50% by mass or more, more preferably 60% by mass or more, more preferably 70% by mass or more, and more preferably 80% by mass or more, from the viewpoint of achieving high adhesive force to the electrically peelable adhesive layer 1. That is, from the viewpoint of achieving high adhesive force to the electrically peelable adhesive layer 1, the ratio of the (meth)acrylic acid alkyl ester having an alkyl group with 1 to 14 carbon atoms in the total amount of the raw material monomers for forming the acrylic polymer is preferably 50% by mass or more, more preferably 60% by mass or more, more preferably 70% by mass or more, and more preferably 80% by mass or more.

[0058] When the electrically peelable adhesive layer 1 contains an acrylic polymer, the acrylic polymer preferably contains a monomer unit derived from a polar group-containing monomer from the viewpoint of achieving high adhesive force to the electrically peelable adhesive layer 1. Examples of the polar group-containing monomer include carboxyl group-containing monomers, methoxy group-containing monomers, hydroxyl group-containing monomers, and vinyl group-containing monomers.

[0059] Examples of carboxyl-containing monomers include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, carboxyethyl (meth)acrylate, and carboxypentyl (meth)acrylate. Among them, acrylic acid and methacrylic acid are preferred. In addition, one carboxyl-containing monomer may be used, or two or more carboxyl-containing monomers may be used.

[0060] As a methoxy group-containing monomer, 2-methoxyethyl acrylate is mentioned, for example.

[0061] As the hydroxyl-containing monomer, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, (4-hydroxymethylcyclohexyl)methyl acrylate, N-hydroxymethyl (meth)acrylamide, vinyl alcohol, allyl alcohol, 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, and diethylene glycol monovinyl ether can be mentioned. Among them, 2-hydroxyethyl (meth)acrylate is preferred. In addition, one hydroxyl-containing monomer can be used, and two or more hydroxyl-containing monomers can also be used.

[0062] As the vinyl-containing monomer, for example, vinyl acetate, vinyl propionate and vinyl laurate can be mentioned. Among them, vinyl acetate is preferred. In addition, one vinyl-containing monomer can be used, or two or more vinyl-containing monomers can be used.

[0063] The proportion of the monomer units derived from the polar group-containing monomer in the acrylic polymer is preferably 0.1% by mass or more from the viewpoint of ensuring cohesion in the electro-peelable adhesive layer 1 and preventing residual adhesive on the surface of the adherend after the electro-peelable adhesive layer 1 is peeled off. That is, from the viewpoint of ensuring cohesion and preventing residual adhesive, the proportion of the polar group-containing monomer in the total amount of raw monomers used to form the acrylic polymer is preferably 0.1% by mass or more. In addition, from the viewpoint of appropriately showing the characteristics of the monomer units derived from the above-mentioned (meth) acrylic acid alkyl ester having an alkyl group with 1 to 14 carbon atoms in the acrylic polymer, the proportion of the monomer units derived from the polar group-containing monomer in the acrylic polymer is preferably 30% by mass or less. That is, from the viewpoint of the presentation of this characteristic, the proportion of the polar group-containing monomer in the total amount of raw monomers used to form the acrylic polymer is preferably 30% by mass or less.

[0064] The method for obtaining the acrylic polymer by polymerizing the above-mentioned monomers is not particularly limited, and a known method can be used. Examples of the polymerization method include solution polymerization, emulsion polymerization, bulk polymerization, and suspension polymerization.

[0065] From the viewpoint of achieving sufficient adhesive force in the electrically-peelable adhesive layer 1, the content of the polymer in the electrically-peelable adhesive layer 1 is preferably 70 mass % or more, more preferably 80 mass % or more, more preferably 85 mass % or more, and more preferably 90 mass % or more.

[0066] The electrolyte contained in the electro-peelable adhesive layer 1 is a substance that can be ionized into anions and cations, and examples of such electrolytes include ionic liquids, alkali metal salts, alkaline earth metal salts, and organic quaternary ammonium salts. From the viewpoint of achieving good electro-peelability in the electro-peelable adhesive layer 1, an ionic liquid is preferably used as the electrolyte contained in the electro-peelable adhesive layer 1. The ionic liquid is a salt that is liquid at room temperature (about 25° C.) and contains anions and cations.

[0067] When the electro-peelable adhesive layer 1 contains an ionic liquid, the anion of the ionic liquid preferably contains an anion selected from the group consisting of (FSO 2 ) 2 N - ,(CF 3 SO 2 ) 2 N - ,(CF 3 CF 2 SO 2 ) 2 N - ,(CF 3 SO 2 ) 3 C - , CH 3 COO - CF 3 COO - CF 3 CF 2 CF 2 COO - CF 3 SO 3 - CF 3 (CF 2 ) 3 SO 3 - Br - 、AlCl 4 - 、Al 2 Cl 7 - 、NO 3 - , BF 4 - PF 6 - , AsF6 - , SbF 6 - , and F(HF) n - (n represents an integer greater than or equal to 1).

[0068] Among them, as anion, (FSO 2 ) 2 N-[bis(fluorosulfonyl)imide anion] and (CF 3 SO 2 ) 2 N-[bis(trifluoromethanesulfonyl)imide anion] is chemically stable and suitable for achieving the electrical peeling property of the electrical peeling adhesive layer 1, and therefore is preferred.

[0069] When the electro-peelable adhesive layer 1 contains an ionic liquid, the cation of the ionic liquid preferably contains at least one selected from the group consisting of imidazolium cations, pyridinium cations, pyrrolidinium cations, and ammonium cations.

[0070] Examples of the imidazolium cation include 1-methylimidazolium cation, 1-ethyl-3-methylimidazolium cation, 1-propyl-3-methylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-pentyl-3-methylimidazolium cation, 1-hexyl-3-methylimidazolium cation, 1-heptyl-3-methylimidazolium cation, 1-octyl-3-methylimidazolium cation, 1-nonyl-3-methylimidazolium cation, 1-undecyl-3-methylimidazolium cation, 1-dodecyl-3-methylimidazolium cation, and the like. imidazolium cation, 1-tridecyl-3-methylimidazolium cation, 1-tetradecyl-3-methylimidazolium cation, 1-pentadecyl-3-methylimidazolium cation, 1-hexadecyl-3-methylimidazolium cation, 1-heptadecyl-3-methylimidazolium cation, 1-octadecyl-3-methylimidazolium cation, 1-undecyl-3-methylimidazolium cation, 1-benzyl-3-methylimidazolium cation, 1-butyl-2,3-dimethylimidazolium cation and 1,3-bis(dodecyl)imidazolium cation.

[0071] Examples of the pyridinium cation include 1-butylpyridinium cation, 1-hexylpyridinium cation, 1-butyl-3-methylpyridinium cation, 1-butyl-4-methylpyridinium cation, and 1-octyl-4-methylpyridinium cation.

[0072] Examples of the pyrrolidinium cation include a 1-ethyl-1-methylpyrrolidinium cation and a 1-butyl-1-methylpyrrolidinium cation.

[0073] Examples of the ammonium cation include a tetraethylammonium cation, a tetrabutylammonium cation, a methyltrioctylammonium cation, a tetradecyltrihexylammonium cation, a glycidyltrimethylammonium cation, and a trimethylaminoethylacrylate cation.

[0074] As the ionic liquid in the electro-peelable adhesive layer 1, it is particularly preferable to contain the above-mentioned (FSO) from the viewpoint of realizing high electro-peelability in the electro-peelable adhesive layer 1 by utilizing the high diffusivity of cations. 2 ) 2 An ionic liquid of N-[bis(fluorosulfonyl)imide anion] and a cation having a molecular weight of 160 or less. Examples of the cation having a molecular weight of 160 or less include 1-methylimidazolium cation, 1-ethyl-3-methylimidazolium cation, 1-propyl-3-methylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-pentyl-3-methylimidazolium cation, 1-butylpyridinium cation, 1-hexylpyridinium cation, 1-butyl-3-methylpyridinium cation, 1-butyl-4-methylpyridinium cation, 1-ethyl-1-methylpyrrolidinium cation, 1-butyl-1-methylpyrrolidinium cation, tetraethylammonium cation, glycidyltrimethylammonium cation, and trimethylaminoethylacrylate cation.

[0075] Examples of commercially available ionic liquids contained in the electro-peelable adhesive layer 1 include "ELEXCEL AS-110", "ELEXCEL MP-442", "ELEXCEL IL-210", "ELEXCEL MP-471", "ELEXCEL MP-456" and "ELEXCEL AS-804" manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.

[0076] When the electro-peelable adhesive layer 1 contains an alkali metal salt, examples of the alkali metal salt include LiCl, Li 2 SO 4 , LiBF 4 、LiPF 6 、LiClO 4 、LiAsF 6 、LiCF 3 SO 3 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 C 2 F 5 ) 2 、LiC(SO 2 CF 3 ) 3 , NaCl, Na 2SO 4 , NaBF 4 、NaPF 6 、NaClO 4 、NaAsF 6 、NaCF 3 SO 3 、NaN(SO 2 CF 3 ) 2 、NaN(SO 2 C 2 F 5 ) 2 、NaC(SO 2 CF 3 ) 3 , KCl, K 2 SO 4 KBF 4 、KPF 6 , KClO 4 , KASF 6 、KCF 3 SO 3 、KN(SO 2 CF 3 ) 2 、KN(SO 2 C 2 F 5 ) 2 and KC(SO 2 CF 3 ) 3 .

[0077] The ionic conductivity of the ionic liquid is preferably 0.1mS / cm or more. More preferably, it is 1mS / cm or more, more preferably 3mS / cm or more, more preferably 5mS / cm or more, more preferably 10mS / cm or more, particularly preferably 15mS / cm or more, and most preferably 20mS / cm or more. There is no particular restriction on the upper limit, and by having the above-mentioned ionic conductivity, the adhesive force will be fully reduced even in the case of low voltage. It should be noted that the ionic conductivity can be measured by AC impedance method using, for example, a 1260 frequency response analyzer manufactured by Solartron.

[0078] In order to impart the electrical stripping property to the electrical stripping adhesive layer 1, for example, the content of the ionic liquid in the electrical stripping adhesive layer 1 is 0.1 parts by mass or more, and from the viewpoint of achieving better electrical stripping property, it is preferably 0.5 parts by mass or more, more preferably 0.6 parts by mass or more, further preferably 0.8 parts by mass or more, particularly preferably 1.0 parts by mass or more, and most preferably 1.5 parts by mass or more. From the viewpoint of achieving good adhesive force and electrical stripping property in a balanced manner for the electrical stripping adhesive layer 1, the content of the ionic liquid in the electrical stripping adhesive layer 1 is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, further preferably 15 parts by mass or less, particularly preferably 10 parts by mass or less, and most preferably 5 parts by mass or less, from the viewpoint of achieving good adhesive force and electrical stripping property in the electrical stripping adhesive layer 1.

[0079] In order to promote the movement of the ionic liquid when the voltage is applied, the electro-peelable adhesive layer 1 may also contain polyethylene glycol, polypropylene glycol or tetraethylene glycol dimethyl ether as needed. As polyethylene glycol, polypropylene glycol or tetraethylene glycol dimethyl ether, substances with a number average molecular weight of 100 to 6000 can be used. The content of these components when contained is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and further preferably 1 part by mass or more relative to 100 parts by mass of the polymer, and is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and further preferably 15 parts by mass or less.

[0080] The electrical stripping adhesive layer 1 may also contain other components within the scope of not damaging the effect of the present invention. As such components, for example, tackifiers, silane coupling agents, colorants, pigments, dyes, surface lubricants, leveling agents, softeners, antioxidants, anti-aging agents, light stabilizers, inhibitors, inorganic or organic fillers, metal powders, particulates, anticorrosives and foils can be cited, and various additives in the resin composition can be used. The content of these components is determined within the scope of not damaging the effect of the present invention according to the purpose of use. For example, it is, for example, less than 10 parts by mass relative to 100 parts by mass of the polymer.

[0081] The thickness of the electrically peelable adhesive layer 1 is not particularly limited, but is preferably 1 μm or more, more preferably 3 μm or more, further preferably 5 μm or more, and particularly preferably 10 μm or more from the viewpoint of achieving good adhesion in the electrically peelable adhesive layer 1. In addition, from the viewpoint of reducing the applied voltage when the adherend is peeled, it is preferably 1000 μm or less, more preferably 500 μm or less, further preferably 100 μm or less, and particularly preferably 50 μm or less.

[0082] Examples of the electro-peelable adhesive layer and the adhesive sheet having the electro-peelable adhesive layer suitable for use in the peeling method described below include the following aspects 1 to 3. In addition, the adhesive sheet having the electro-peelable adhesive layer may be simply referred to as an adhesive sheet.

[0083] The adhesive sheet of the present embodiment is not particularly limited as long as it has at least one layer of the above-mentioned electrical stripping adhesive layer. The adhesive sheet of the present embodiment may have an adhesive layer (hereinafter, sometimes referred to as "other adhesive layers") that does not contain electrolyte other than the electrical stripping adhesive layer. The adhesive sheet of the present embodiment may also have a substrate, a conductive layer, a substrate for conducting electricity, an intermediate layer and a primer layer in addition to the above. The adhesive sheet of the present embodiment can be, for example, in the form of a roll or a sheet. It should be noted that the meaning of "adhesive sheet" also includes "adhesive tape". That is, the adhesive sheet of the present embodiment can be an adhesive tape in a strip-shaped form.

[0084] The adhesive sheet of the present embodiment may be a double-sided adhesive sheet without a substrate and formed only by an electrical stripping adhesive layer, i.e., without a substrate layer (no substrate). The adhesive sheet of the present embodiment may also be a double-sided adhesive sheet having a substrate and both sides of the substrate being an adhesive layer (electrically stripping adhesive layer or other adhesive layer). In addition, the adhesive sheet of the present embodiment may also be a single-sided adhesive sheet having a substrate and an electrical stripping adhesive layer laminated on one side of the substrate. It should be noted that the adhesive sheet of the present embodiment may have a diaphragm (peeling liner) for protecting the surface of the adhesive layer, but the diaphragm is not included in the adhesive sheet of the present embodiment.

[0085] As the substrate, there is no particular limitation, and examples include paper substrates such as paper, fiber substrates such as cloth and nonwoven fabrics, plastic substrates such as films and sheets based on various plastics (polyolefin resins such as polyethylene and polypropylene, polyester resins such as polyethylene terephthalate, acrylic resins such as polymethyl methacrylate, etc.), and laminates thereof. The substrate may have a single layer or a multilayered layer. It should be noted that various treatments such as back treatment, antistatic treatment, and primer treatment may be applied to the substrate as needed.

[0086] The conductive layer is not particularly limited as long as it is a conductive layer, and may be a metal substrate such as a metal (e.g., aluminum, magnesium, copper, iron, tin, gold, etc.) foil or a metal plate (e.g., aluminum, magnesium, copper, iron, tin, silver, etc.). Furthermore, the conductive layer may be a conductive polymer or a metal vapor-deposited film provided on a substrate.

[0087] The substrate for conducting electricity is not particularly limited as long as it is a substrate having a conductive layer (conducting electricity), and examples thereof include a substrate having a conductive layer such as a metal layer laminated on the surface of the substrate, and examples thereof include a substrate having a metal layer formed on the surface of the substrate exemplified above by plating, chemical vapor deposition, sputtering, etc. Examples thereof include the metals, metal plates, conductive polymers, etc. exemplified above.

[0088] From the perspective of adhesion when no voltage is applied, the thickness of the electrically peelable adhesive layer is preferably 1 μm or more and 1000 μm or less. The upper limit of the thickness is more preferably 500 μm, further preferably 100 μm, and particularly preferably 30 μm, and the lower limit is more preferably 3 μm, further preferably 5 μm, and particularly preferably 8 μm. It should be noted that when the adhesive sheet is a substrate-free double-sided adhesive sheet obtained by only one electrically peelable adhesive layer, the thickness of the electrically peelable adhesive layer is the thickness of the adhesive sheet.

[0089] The components and contents contained in the other adhesive layers may be the same as those described above regarding the components and contents contained in the electro-peelable adhesive layer, except for the electrolyte.

[0090] From the perspective of adhesiveness, the thickness of the other adhesive layer is preferably 1 μm to 2000 μm, the upper limit of which is more preferably 1000 μm, further preferably 500 μm, particularly preferably 100 μm, and the lower limit is more preferably 3 μm, further preferably 5 μm, particularly preferably 8 μm.

[0091] The thickness of the substrate is preferably 10 μm or more and 1000 μm or less. The upper limit of the thickness is more preferably 500 μm, further preferably 300 μm, and particularly preferably 100 μm, and the lower limit is more preferably 12 μm, further preferably 25 μm.

[0092] The thickness of the conductive layer is preferably 0.001 μm to 1000 μm, and the upper limit is more preferably 500 μm, further preferably 300 μm, further preferably 50 μm, further preferably 10 μm, and the lower limit is more preferably 0.01 μm, further preferably 0.03 μm, further preferably 0.05 μm.

[0093] The thickness of the conducting substrate is preferably 10 μm or more and 1000 μm or less. The upper limit of the thickness is more preferably 500 μm, further preferably 300 μm, and particularly preferably 100 μm, and the lower limit is more preferably 12 μm, further preferably 25 μm.

[0094] The surface of the electrically peelable adhesive layer and other adhesive layers of the adhesive sheet of this embodiment can be protected by a separator (release liner). As the separator, there is no particular limitation, and examples include a release liner whose surface is treated with silicone on a substrate (liner substrate) such as paper or plastic film, and a release liner whose surface is laminated with a polyolefin resin on a substrate (liner substrate) such as paper or plastic film. The thickness of the separator is not particularly limited, but is preferably 10 μm or more and 100 μm or less.

[0095] As a first aspect, there can be mentioned an electro-peelable adhesive layer including a polymer, an electrolyte, and a thermally expandable filler, and a pressure-sensitive adhesive sheet having the electro-peelable adhesive layer.

[0096] Here, various suitable examples of the polymer, electrolyte, other optional components, etc. in the electro-peelable adhesive layer and the adhesive sheet of the first embodiment are as described above.

[0097] The first embodiment of the electrically exfoliative adhesive layer and adhesive sheet contains a thermally expansive filler. A thermally expansive filler is a filler that can expand or foam by heating. The electrically exfoliative adhesive layer and adhesive sheet containing the thermally expansive filler produce irregularities on the adhesive surface by heating to reduce the adhesive force, so that the adhesive force is sufficient when the adhesive force is required, and the peeling property is excellent when peeling is required.

[0098] In addition, the electro-peelable adhesive layer and the adhesive sheet of the first embodiment contain an electrolyte such as an ionic liquid and therefore also have electro-peelable properties.

[0099] The content ratio of the above-mentioned heat-expandable filler can be appropriately set according to the desired reduction of the adhesive force, etc. The content ratio of the heat-expandable filler is preferably 5 to 50 parts by mass relative to 100 parts by mass of the polymer in the adhesive, more preferably 10 to 45 parts by mass, further preferably 15 to 40 parts by mass, and particularly preferably 20 to 30 parts by mass. If it is such a range, the electrical peeling property of the adhesive layer can be maintained, and a smooth adhesive layer can be formed before the foaming of the heat-expandable filler, and an adhesive layer with good concavoconvex surface can be formed after the foaming of the heat-expandable filler.

[0100] From the viewpoint of forming an adhesive layer having a good concavoconvex surface after foaming of the thermally expandable filler, the content ratio of the thermally expandable filler is preferably 5 to 60 parts by mass, more preferably 10 to 55 parts by mass, further preferably 20 to 45 parts by mass, and particularly preferably 30 to 40 parts by mass relative to 100 parts by mass of the polymer in the adhesive.

[0101] As above-mentioned heat-expandable filler, any appropriate heat-expandable filler can be used.As above-mentioned heat-expandable filler, for example, can use the microsphere that the material that will easily expand by heating is enclosed in the shell with elasticity and obtains.Such heat-expandable filler can be manufactured by any appropriate method such as coagulation method, interfacial polymerization method etc.

[0102] Substances that easily expand by heating include, for example, propane, propylene, butene, n-butane, isobutane, isopentane, neopentane, n-pentane, n-hexane, isohexane, heptane, octane, petroleum ether, methane halides, tetraalkylsilane and other low-boiling liquids; azodicarbonamide that is gasified by thermal decomposition; and the like.

[0103] As the material constituting the shell, there can be mentioned polymers composed from nitrile monomers such as acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, α-ethoxyacrylonitrile, and fumaronitrile; carboxylic acid monomers such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and citraconic acid; vinylidene chloride; vinyl acetate; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and β-carboxyethyl acrylate; styrene monomers such as styrene, α-methylstyrene, and chlorostyrene; amide monomers such as acrylamide, substituted acrylamide, methacrylamide, and substituted methacrylamide; etc. The polymer composed of these monomers may be a homopolymer or a copolymer. Examples of the copolymer include vinylidene chloride-methyl methacrylate-acrylonitrile copolymers, methyl methacrylate-acrylonitrile-methacrylonitrile copolymers, methyl methacrylate-acrylonitrile copolymers, and acrylonitrile-methaconic acid copolymers.

[0104] As the thermally expandable filler, an inorganic foaming agent or an organic foaming agent may be used. Examples of the inorganic foaming agent include ammonium carbonate, ammonium bicarbonate, sodium bicarbonate, ammonium nitrite, sodium borohydride, and various azides. In addition, examples of organic foaming agents include chlorofluorinated alkane compounds such as trichloromonofluoromethane and dichloromonofluoromethane; azo compounds such as azobisisobutyronitrile, azodicarbonamide, and barium azodicarboxylate; hydrazine compounds such as p-toluenesulfonylhydrazine, diphenylsulfone-3,3'-disulfonylhydrazine, 4,4'-oxybis(benzenesulfonylhydrazine), and allylbis(sulfonylhydrazine); semicarbazide compounds such as p-toluenesulfonylsemicarbazide and 4,4'-oxybis(benzenesulfonylsemicarbazide); triazole compounds such as 5-morpholino-1,2,3,4-thiatriazole; N-nitroso compounds such as N,N'-dinitrosopentamethylenetetramine and N,N'-dimethyl-N,N'-dinitrosoterephthalamide; and the like.

[0105] The above-mentioned heat-expandable filler can also use a commercially available product. As a specific example of the heat-expandable filler of a commercially available product, the trade name "Matsumoto Microsphere" (grade: F-30, F-30D, F-36D, F-36LV, F-50, F-50D, F-65, F-65D, FN-100SD, FN-100SS, FN-100SSD, FN-180SS, FN-180SSD, F-190D, F-260D, F-2800D) manufactured by Matsumoto Oil Pharmaceutical Co., Ltd., the trade name "EXPANCEL" (grade: 053-40, 031-40, 920-40, 909-80, 930-120) manufactured by Japan Fillite Co., Ltd., the trade name "Die 1000" (grade: 053-40, 031-40, 920-40, 909-80, 930-120) manufactured by Kureha Chemical Industry Co., Ltd. foam (ダイフォーム)" (grades: H750, H850, H1100, S2320D, S2640D, M330, M430, M520), Sekisui Chemical "ADVANCELL" (grades: EML101, EMH204, EHM301, EHM302, EHM303, EM304, EHM401, EM403, EM501), etc.

[0106] The volume cumulative particle size D50 (particle size when the volume is accumulated to 50%) of the thermally expandable filler is preferably 5 μm to 50 μm, more preferably 8 μm to 40 μm, further preferably 10 μm to 30 μm, and particularly preferably 15 μm to 25 μm. If it is within such a range, an adhesive sheet can be obtained in which the electrical peelability of the adhesive layer is maintained and the adhesive expansion is ideally adjusted to prevent the tilt of the adherend during peeling.

[0107] In addition, after the thermally expandable filler is foamed, from the viewpoint of forming an adhesive layer with a good concave-convex surface, the volume cumulative particle size D50 (particle size when the volume is accumulated to 50%) of the thermally expandable filler is preferably 5 μm to 60 μm, more preferably 10 μm to 50 μm, further preferably 20 μm to 45 μm, and particularly preferably 30 μm to 40 μm.

[0108] The conditions for the heat treatment when using the electropeelable adhesive layer containing a thermally expandable filler can be selected so as to appropriately exert the peeling force reduction effect based on the heat treatment. The temperature of the heat treatment is, for example, 70 to 270° C., preferably 110 to 150° C. The time of the heat treatment is, for example, 30 seconds to 10 minutes, preferably 1 to 5 minutes.

[0109] In addition, as a second aspect, there can be mentioned an electro-peelable adhesive layer which contains a polymer and an electrolyte and is cured by irradiation with active energy rays or heating, and a pressure-sensitive adhesive sheet having the electro-peelable adhesive layer.

[0110] Hereinafter, the adhesive layer cured by irradiation with active energy rays is referred to as an "active energy ray-curable adhesive layer". It should be noted that in this specification, the so-called "active energy ray" is a concept including light such as ultraviolet rays, visible rays, infrared rays, α rays, β rays, γ rays, electron rays, neutron rays, X-rays, and the like.

[0111] In addition, the adhesive layer cured by heating is hereinafter referred to as a "thermosetting adhesive layer".

[0112] That is, the electro-peelable adhesive layer according to the second embodiment has the electro-peelable property of an electro-peelable adhesive layer and also has the property of being cured by irradiation with active energy rays or heating as an "active energy ray-curable adhesive layer" or a "thermosetting adhesive layer".

[0113] (Active Energy Ray-Curing Adhesive Layer)

[0114] As a suitable example of an active energy ray-curable adhesive layer, an adhesive layer that exhibits curability by including a carbon-carbon double bond in the adhesive layer can be cited. The carbon-carbon double bond does not react with moisture, acidity, etc. in the air under a normal storage environment applicable in industry, and is chemically stable. On the other hand, if free radicals are generated by irradiation with active energy rays, a reaction (such as a polymerization reaction, a cross-linking reaction) occurs and solidifies. From the viewpoint of ease of operation, light (such as ultraviolet rays) can be cited as a preferred active energy ray.

[0115] In the adhesive layer that exhibits curability by including carbon-carbon double bonds, the presence of carbon-carbon double bonds in the adhesive layer is not particularly limited. The carbon-carbon double bonds may be included in the adhesive layer in the form of, for example, a polymer having a carbon-carbon double bond (e.g., a base polymer), a monomer having a carbon-carbon double bond (e.g., an unreacted multifunctional monomer as described above), etc. These may be used alone or in combination of two or more.

[0116] The form of the carbon-carbon double bond contained in the polymer and the form of the carbon-carbon double bond contained in the monomer are not particularly limited. For example, the carbon-carbon double bond may be present in the polymer or monomer in the form of an ethylenically unsaturated group. Examples of ethylenically unsaturated groups include (meth)acryloyl, vinyl, allyl, methallyl, etc. From the viewpoint of reactivity, (meth)acryloyl is preferred.

[0117] (Polymers with carbon-carbon double bonds)

[0118] In some embodiments, the active energy ray-curable adhesive layer preferably includes a polymer having a carbon-carbon double bond. Hereinafter, the polymer having a carbon-carbon double bond is also referred to as "polymer (PD)". For example, a polymer (PD) having a carbon-carbon double bond in the form of an ethylenically unsaturated group is preferred. In some preferred embodiments, the polymer (PD) may be included in the active energy ray-curable adhesive layer as a base polymer of the adhesive layer. In other embodiments, the polymer (PD) may be included in the active energy ray-curable adhesive layer as a secondary component used on the basis of a base polymer that does not contain a carbon-carbon double bond. It may also be an active energy ray-curable adhesive layer that includes a polymer (PD) as a base polymer and further includes a monomer having a carbon-carbon double bond (e.g., an unreacted multifunctional monomer) as a secondary component.

[0119] The form of the carbon-carbon double bond possessed by the polymer (PD) is not particularly limited. The polymer (PD) may be a polymer having a carbon-carbon double bond in a side chain, or a polymer having a carbon-carbon double bond in a main chain. Here, the so-called having a carbon-carbon double bond in the main chain includes the presence of a carbon-carbon double bond in the main chain skeleton of the polymer (PD) and the presence of a carbon-carbon double bond at the end of the main chain. From the viewpoint of the reactivity of the carbon-carbon double bond, a polymer (PD) having a carbon-carbon double bond in a side chain may be preferably used. The method for making the polymer (PD) contain a carbon-carbon double bond is not particularly limited, and an appropriate method may be selected from methods known to those skilled in the art.

[0120] The polymer (PD) is not particularly limited, and an appropriate polymer can be selected and used in consideration of the characteristics of the adhesive layer, etc. As the polymer (PD), a polymer (secondary polymer) obtained by introducing carbon-carbon double bonds into a polymer (primary polymer) that does not contain carbon-carbon double bonds or has a carbon-carbon double bond content less than the target product by chemical modification or the like can be preferably used.

[0121] As a specific example of a method for introducing a carbon-carbon double bond into a primary polymer, the following method can be cited, wherein a primary polymer copolymerized with a monomer having a functional group (functional group A) is prepared, and a compound having a functional group (functional group B) capable of reacting with the functional group A and a carbon-carbon double bond in one molecule (hereinafter also referred to as "unsaturated compound containing functional group B") is reacted with the primary polymer in a manner that the carbon-carbon double bond does not disappear. The reaction between the functional group A and the functional group B is preferably a reaction that is not accompanied by the generation of free radicals, such as a condensation reaction and an addition reaction.

[0122] As examples of the combination of functional group A and functional group B, the combination of carboxyl and epoxy, the combination of carboxyl and aziridine, the combination of hydroxyl and isocyanate, etc. can be cited. Among them, from the viewpoint of reaction tracking, the combination of hydroxyl and isocyanate is preferred. In addition, the combination of the above-mentioned functional groups A and B can be any combination that can obtain a polymer with a carbon-carbon double bond. The functional group of one side in the above-mentioned combination can be used as functional group A, and the other side can be used as functional group B, or the functional group of the above-mentioned one side can be used as functional group B, and the other side can be used as functional group A. For example, when explaining the combination of hydroxyl and isocyanate, functional group A can be hydroxyl (in this case, functional group B becomes isocyanate), or it can be isocyanate (in this case, functional group B is hydroxyl). Among them, it is preferred that the primary polymer has a hydroxyl group and the above-mentioned compound has an isocyanate combination. This combination is particularly preferred when the primary polymer is an acrylic polymer.

[0123] In addition, using vinyl alcohol polymer (typically polyvinyl alcohol) as the above-mentioned primary polymer, making halogenated vinyl such as vinyl bromide, halogenated allyl such as allyl bromide react with the vinyl alcohol polymer (typically vinyl alcohol polymer without carbon-carbon double bond), this method can also be used as a suitable example of the method for obtaining a polymer with carbon-carbon double bond. In this method, the above-mentioned reaction is carried out under appropriate alkaline conditions, and through this reaction, a vinyl alcohol polymer containing vinyl in the side chain can be obtained. In addition, for example, the method for preparing a polymer with carbon-carbon double bond by using the microorganism producing polymer disclosed in Japanese Patent Gazette No. 4502363 can also be adopted. The various conditions such as microbial species and microbial culture conditions in this method can adopt the conditions recorded in the above-mentioned patent gazette, or be set by appropriately changing etc. within the scope of the technical common sense of those skilled in the art.

[0124] From the viewpoint of the reactivity of the two, the molar mass (M A ) and the molar mass of functional group B (M B ) molar ratio (M A / M B ) is usually set to be 0.2 or more, and can be 0.5 or more, 0.7 or more, or 1.0 or more. In some embodiments, the molar ratio (M A / M B ) may be greater than 1.0, greater than 1.5, or greater than 2.0. For example, when the functional group A is used for other reactions (crosslinking reaction with a crosslinking agent, etc.), it is preferred to make the molar ratio (M A / M B ) exceeds 1.0. In addition, the molar ratio (M A / M B) may be, for example, 20 or less. In some embodiments, from the viewpoint of achieving a good balance between adhesion to an adherend before light irradiation and peelability from the adherend after light irradiation (for example, peelability by water peeling), the molar ratio (M A / M B ) is preferably less than 10, may be less than 5.0, may be less than 2.5, may be less than 1.8, may be less than 1.5, or may be less than 1.3.

[0125] The amount of the compound having a functional group B and a carbon-carbon double bond (hereinafter also referred to as "unsaturated compound containing a functional group B") used is such that the above molar ratio (M A / M B ), for example, it can be 1.0 parts by weight or more, 3.0 parts by weight or more, 5.0 parts by weight or more, or 7.0 parts by weight or more relative to 100 parts by weight of the primary polymer having the functional group A. From the viewpoint of taking into account both the adhesion before light irradiation and the peelability after light irradiation (for example, peelability based on water peeling) at a higher level, in some embodiments, the amount of the unsaturated compound containing the functional group B relative to 100 parts by weight of the above-mentioned primary polymer is preferably 9.0 parts by weight or more, more preferably 10 parts by weight or more, 12 parts by weight or more, 14 parts by weight or more, or 16 parts by weight or more. In addition, the amount of the unsaturated compound containing the functional group B relative to 100 parts by weight of the above-mentioned primary polymer can be set to less than 40 parts by weight, and it is usually appropriate to set it to less than 35 parts by weight, preferably less than 30 parts by weight, and can be less than 25 parts by weight, or less than 20 parts by weight. In some embodiments, the amount of the unsaturated compound containing the functional group B based on 100 parts by weight of the primary polymer may be less than 18 parts by weight, less than 16 parts by weight, less than 13 parts by weight, less than 10 parts by weight or less than 7 parts by weight.

[0126] As a suitable example of a polymer having a carbon-carbon double bond, an acrylic polymer having a (meth)acryloyl group introduced into a side chain can be cited. Such an acrylic polymer can be obtained, for example, by reacting an acrylic primary polymer having a hydroxyl group (functional group A) introduced by copolymerization with a compound having a carbon-carbon double bond and an isocyanate group (functional group B) in such a manner that the carbon-carbon double bond does not disappear.

[0127] In addition, the polymer having a carbon-carbon double bond may be, for example, a diene polymer (typically a conjugated diene polymer). A diene polymer (typically a conjugated diene polymer) is typically a polymer obtained by polymerizing or copolymerizing a diene (typically a conjugated diene). Examples of the diene polymer (typically a conjugated diene polymer) include butadiene polymers such as polybutadiene and styrene butadiene copolymers; isoprene polymers such as polyisoprene and styrene isoprene copolymers; chloroprene polymers such as polychloroprene; and the like.

[0128] As another example of an active energy ray-curable adhesive layer, an adhesive layer containing a polymer having a structure that causes a crosslinking reaction by irradiation with active energy rays and having a structure other than a carbon-carbon double bond can be cited. For example, an adhesive containing a polymer having a benzophenone structure in a side chain can exhibit active energy ray curability by photocrosslinking using the benzophenone structure. As a polymer having a benzophenone structure in a side chain, an acrylic polymer having a benzophenone structure in a side chain can be preferably used.

[0129] (Photoinitiator)

[0130] When ultraviolet rays are used as the active energy rays for curing the active energy ray-curable adhesive layer, it is preferred that the adhesive layer contain a photoinitiator from the viewpoint of promoting the reaction or improving the efficiency of using light energy.

[0131] Examples of the photoinitiator include benzoin ether photoinitiators, acetophenone photoinitiators, α-hydroxyketone photoinitiators, aromatic sulfonyl chloride photoinitiators, photoactive oxime photoinitiators, benzoin photoinitiators, benzyl photoinitiators, benzophenone photoinitiators, ketal photoinitiators, thioxanthone photoinitiators, α-aminoketone photoinitiators, acylphosphine oxide photoinitiators, etc. The photoinitiator may be used alone or in combination of two or more.

[0132] Examples of benzoin ether-based photoinitiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of acetophenone-based photoinitiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxy-cyclohexyl-phenyl ketone, 4-phenoxydichloroacetophenone, and 4-tert-butyl-dichloroacetophenone. Examples of α-hydroxyketone-based photoinitiators include 2-hydroxy-2-methyl-1-phenyl-propane-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, and the like. Examples of aromatic sulfonyl chloride-based photoinitiators include 2-naphthalenesulfonyl chloride, and the like. As photoactive oxime-based photoinitiators, for example, 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime, etc. can be mentioned. As benzoin-based photoinitiators, for example, benzoin, etc. can be mentioned. As benzyl-based photoinitiators, for example, benzyl, etc. can be mentioned. As benzophenone-based photoinitiators, for example, benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenylketone, etc. can be mentioned. As ketal-based photoinitiators, for example, benzyl dimethyl ketal, etc. can be mentioned. As thioxanthone-based photoinitiators, for example, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, dodecylthioxanthone, etc. can be mentioned. Examples of α-aminoketone-based photoinitiators include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1. Examples of acylphosphine oxide-based photoinitiators include 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide.

[0133] As the photoinitiator, commercially available products can be used, for example, trade names "Omnirad 651", "Omnirad 184", "Omnirad 2959", "Omnirad 907", "Omnirad 369", "Omnirad 1173", "Omnirad TPO" and the like manufactured by IGM Regins.

[0134] In some embodiments, as a photoinitiator, a photoinitiator that is not easily decomposed or generates free radicals by heating can be preferably used. For example, as a photoinitiator, a heat-resistant photoinitiator with a 10% reduction temperature of 200°C or more can be used. By using such a heat-resistant photoinitiator, even if it is exposed to high temperature before the curing process, it is not easy to damage the effect of reducing the peeling force of the curing process based on the active energy line. It should be noted that the 10% reduction temperature refers to the ambient temperature at the moment when the weight of the photoinitiator is reduced by 10% by weight relative to the weight before the temperature rise (that is, the weight of the photoinitiator becomes 90% by weight relative to the weight before the temperature rise) when the ambient temperature rises from 23°C to 300°C at a heating rate of 2°C / min under a nitrogen atmosphere. The 10% reduction temperature of the photoinitiator is more preferably above 210°C, and more preferably above 220°C. Examples of photoinitiators having a 10 wt % reduction temperature within such a range include "Omnirad 369", "Omnirad 127", "Omnirad 379", and "Omnirad 819" manufactured by IGM Regins; "IRGACURE OXE02" manufactured by BASF Japan; "ESACURE one" and "ESACURE 1001m" manufactured by Lamberti; and "Adeka optomer N-1414", "Adeka optomer N-1606", and "Adeka optomer N-1717" manufactured by Asahi Denka Industries.

[0135] The adhesive layer containing a photoinitiator can be formed using an adhesive composition containing the photoinitiator. The method for making the adhesive composition contain a photoinitiator is not particularly limited. For example, it is preferred to add a mixed photoinitiator to the adhesive composition, typically in a liquid containing a polymer (polymer when polymerization is completed). In this method, the photoinitiator can be added to the composition together with other added components (such as a cross-linking agent, etc.). As another method, a method of adding a polymerization initiator that can function as a photoinitiator during polymer polymerization can be exemplified. In this method, the polymerization initiator is added in a manner that a specified amount remains after polymerization. The residual amount of the polymerization initiator (the amount of the photoinitiator present) can be adjusted not only by the amount of the polymerization initiator added, but also by the polymer polymerization conditions, the drying conditions when the adhesive layer is formed, the curing conditions, etc.

[0136] In the case where the adhesive layer contains a photoinitiator, the content of the photoinitiator in the adhesive layer is not particularly limited and can be set in a manner that appropriately exerts the desired effect. In some embodiments, the content of the photoinitiator can be, for example, about 0.05 parts by weight or more, preferably about 0.1 parts by weight or more, and more preferably about 0.5 parts by weight or more relative to 100 parts by weight of the base polymer of the adhesive layer. By increasing the content of the photoinitiator, there is a tendency for the active energy line curing property of the adhesive layer to be improved. In some embodiments, the content of the photoinitiator relative to 100 parts by weight of the base polymer can be, for example, about 0.8 parts by weight or more, or about 2.0 parts by weight or more, or about 2.5 parts by weight or more. In addition, the content of the photoinitiator relative to 100 parts by weight of the base polymer can be set to, for example, about 20 parts by weight or less, and it is usually appropriate to set it to about 10 parts by weight or less, preferably about 8 parts by weight or less, can be set to about 6 parts by weight or less, and can also be set to about 4 parts by weight or less. From the viewpoint of storage stability of the PSA layer or PSA sheet (for example, the ability to suppress performance changes caused by storage of the PSA sheet before attachment to an adherend), it is preferred that the content of the photoinitiator is not too high.

[0137] (irradiation conditions)

[0138] The irradiation conditions of the active energy ray are not particularly limited and can be set so that the curing of the adhesive layer is appropriately performed. A person skilled in the art can set appropriate irradiation conditions without excessive burden based on the technical common sense in the field, so detailed description is omitted. As an example, when UV is used as the active energy ray, the UV irradiation conditions can be set to, for example, a cumulative light amount of about 50 mJ / cm 2 ~About 5000mJ / cm 2 Range, about 50mJ / cm 2 ~About 2000mJ / cm 2 range, or about 100 mJ / cm 2 ~About 2000mJ / cm 2 The irradiation time can be set in the range of about 1 second to about 30 minutes.

[0139] (Thermosetting adhesive layer)

[0140] The thermosetting adhesive layer is typically cured by forming a crosslinked structure by reacting the thermosetting functional group using heat. In order to promote the reaction of the above-mentioned thermosetting functional group, a curing catalyst can be contained in the thermosetting adhesive layer as needed. For example, in a thermosetting adhesive layer containing a carbon-carbon double bond (ethylenically unsaturated group, etc.) as a thermosetting functional group, a known thermal polymerization initiator such as an azo polymerization initiator and a peroxide initiator can be contained as a curing catalyst. The composition of the thermosetting adhesive layer and the conditions of the heat treatment as a means of reducing the peeling force can be selected in a manner that appropriately exerts the peeling force reducing effect brought about by the heat treatment.

[0141] In addition, as a third aspect, there can be mentioned an electrically peelable adhesive layer comprising a polymer, an electrolyte, and at least one compound selected from the group consisting of a surfactant and a compound having a polyoxyalkylene skeleton, and a pressure-sensitive adhesive sheet having the electrically peelable adhesive layer.

[0142] Here, various suitable examples of the polymer, electrolyte, other optional components, etc. in the electro-peelable adhesive layer and the adhesive sheet of the third embodiment are as described above.

[0143] The third embodiment of the electro-peelable adhesive layer and adhesive sheet comprises at least one compound selected from the group consisting of a surfactant and a compound having a polyoxyalkylene skeleton (hereinafter also referred to as compound A or a peeling additive). By containing the compound A (peeling additive) in the adhesive layer, the effect of reducing the peeling force by supplying a peeling liquid can be appropriately presented. The reason is believed to be that for surfactants and compounds having a polyoxyalkylene skeleton, they all have hydrophilic regions, which are moderately biased on the surface of the adhesive layer, and the peeling force is effectively reduced when in contact with the peeling liquid, but this reason is not particularly limited to interpretation.

[0144] In addition, the electro-peelable pressure-sensitive adhesive layer and pressure-sensitive adhesive sheet of the third embodiment contain an electrolyte such as an ionic liquid and therefore also have electro-peelable properties.

[0145] As a stripping liquid, a stripping liquid containing a small amount of additives as needed in water or a mixed solvent with water as the main component can be used. As a solvent other than water constituting the above-mentioned mixed solvent, a lower alcohol (such as ethanol), a lower ketone (such as acetone), etc. that can be uniformly mixed with water can be used. As the above-mentioned additives, known surfactants, pH adjusters, etc. can be used. From the viewpoint of avoiding contamination of the adherend, in some embodiments, it is preferred to use a stripping liquid that does not substantially contain additives. From the viewpoint of environmental hygiene, it is particularly preferred to use water as the stripping liquid. There is no particular limitation as water, and considering the purity required according to the application, ease of acquisition, etc., for example, distilled water, ion exchange water, tap water, etc. can be used.

[0146] When the stripping method disclosed herein is implemented by supplying a stripping liquid, the stripping liquid is preferably supplied to the stripping front line of the adhesive sheet from the adherend. Here, in this specification, the stripping front line refers to the part where the adhesive surface of the adhesive sheet begins to separate from the adherend when the adhesive sheet is stripped from the adherend. In addition, it is preferred that the stripping front line where the adhesive sheet is stripped from the adherend is in a state where a stripping liquid exists at the interface between the adherend and the adhesive sheet, and the adhesive sheet is stripped from the adherend while following the movement of the stripping front line, while the stripping liquid enters the interface.

[0147] As surfactants and compounds with polyoxyalkylene skeletons, one or more of known surfactants and compounds with polyoxyalkylene skeletons can be used without particular limitation. Compound A is typically preferably included in the adhesive layer in a free form. It should be noted that among the above-mentioned surfactants, there are compounds with polyoxyalkylene skeletons, and vice versa.

[0148] As the surfactant that can be used as compound A, known nonionic surfactants, anionic surfactants, cationic surfactants, etc. can be used. Among them, nonionic surfactants are preferred. The surfactant can be used alone or in combination of two or more.

[0149] Examples of nonionic surfactants include polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether and the like; polyoxyethylene alkylphenyl ethers such as polyoxyethylene octylphenyl ether and polyoxyethylene nonylphenyl ether; polyoxyethylene fatty acid esters such as polyoxyethylene monolaurate, polyoxyethylene monostearate, and polyoxyethylene monooleate; sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, and sorbitan monooleate; Sorbitan fatty acid esters such as sorbitan monooleate; polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan triisostearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate and other polyoxyethylene sorbitan fatty acid esters; polyoxyethylene glycerol ether fatty acid esters; polyoxyethylene-polyoxypropylene block copolymers; etc. The nonionic surfactant may be a reactive surfactant having a free radical polymerizable functional group such as acryl, (meth)allyl, vinyl, (meth)acryloyl (for example, a nonionic reactive surfactant such as polyoxyethylene nonylpropenylphenyl ether). These nonionic surfactants may be used alone or in combination of two or more. From the viewpoint of properly exerting the effect of Compound A being appropriately localized on the PSA layer surface and improving the performance stability of the PSA sheet, a (non-reactive) nonionic surfactant having no radical polymerizable functional group as described above can be preferably used.

[0150] Examples of the anionic surfactant include: alkylbenzene sulfonates such as nonylbenzene sulfonate and dodecylbenzene sulfonate (e.g., sodium dodecylbenzene sulfonate); alkyl sulfates such as lauryl sulfate (e.g., sodium lauryl sulfate, ammonium lauryl sulfate) and octadecyl sulfate; fatty acid salts; polyoxyethylene alkyl ether sulfates such as polyoxyethylene octadecyl ether sulfate and polyoxyethylene lauryl ether sulfate (e.g., sodium polyoxyethylene alkyl ether sulfate); polyoxyethylene alkyl phenyl ether sulfates such as polyoxyethylene lauryl phenyl ether sulfate (e.g., octadecyl ether sulfate); Such as polyoxyethylene alkylphenyl ether ammonium sulfate, polyoxyethylene alkylphenyl ether sodium sulfate, etc.), polyoxyethylene styrenated phenyl ether sulfate and other polyoxyethylene ether sulfates; polyoxyethylene stearyl ether phosphate, polyoxyethylene lauryl ether phosphate and other polyoxyethylene alkyl ether phosphates; polyoxyethylene alkyl ether phosphate salts such as sodium salts and potassium salts of the above polyoxyethylene alkyl ether phosphates; sulfosuccinates such as lauryl sulfosuccinate and polyoxyethylene lauryl sulfosuccinate (for example, sodium polyoxyethylene alkyl sulfosuccinate); polyoxyethylene alkyl ether acetate; etc. In the case where the anionic surfactant forms a salt, the salt may be, for example, a metal salt (preferably a monovalent metal salt), ammonium salt, amine salt, etc., such as a sodium salt, potassium salt, calcium salt, magnesium salt, etc. The anionic surfactant may be used alone or in combination of two or more. From the same viewpoint as the nonionic surfactant, a non-reactive anionic surfactant may be preferably used.

[0151] Examples of the cationic surfactant include polyetheramines such as polyoxyethylene laurylamine and polyoxyethylene stearylamine. The cationic surfactant may be used alone or in combination of two or more.

[0152] As compounds having a polyoxyalkylene skeleton that can be used as compound A, polyalkylene glycols such as polyethylene glycol (PEG) and polypropylene glycol (PPG) can be cited; polyethers containing polyoxyethylene units, polyethers containing polyoxypropylene units, compounds containing oxyethylene units and oxypropylene units (the arrangement of these units can be random or block-shaped); their derivatives; etc. In addition, compounds having a polyoxyalkylene skeleton in the above-mentioned nonionic, anionic, and cationic surfactants can also be used. They can be used alone or in combination of two or more. Among them, it is preferred to use a compound containing a polyoxyethylene skeleton (also called a polyoxyethylene segment), and PEG is more preferred.

[0153] The molecular weight (chemical formula weight) of the compound (e.g., polyethylene glycol) having a polyoxyalkylene skeleton is not particularly limited. From the viewpoint of uniform miscibility, for example, less than 1000 is appropriate, preferably about 600 or less (e.g., 500 or less). The lower limit of the molecular weight of the compound (e.g., polyethylene glycol) having a polyoxyalkylene skeleton is not particularly limited, and preferably uses a compound having a molecular weight of about 100 or more (e.g., about 200 or more, further about 300 or more).

[0154] The adhesive layer containing compound A is typically formed by an adhesive composition containing the compound A. The adhesive composition containing compound A can be preferably prepared by a method including adding compound A in a solvent-free manner or adding compound A in the form of an organic solvent solution. The above-mentioned solvent-free manner refers to a method that is not diluted by an organic solvent or water that does not form an adhesive layer, for example, it can be a method formed by compound A. The organic solvent used in the preparation of the above-mentioned organic solvent solution can be appropriately selected from the organic solvents known in the past. As a specific example of the organic solvent, the same solvent as the solvent used in the solution polymerization described later can be cited. As a suitable example, ethyl acetate, a mixed solvent containing ethyl acetate (which can be a mixed solvent of ethyl acetate and toluene.), toluene, and a mixed solvent containing toluene can be cited. For example, ethyl acetate or a mixed solvent with ethyl acetate as the main component can be preferably used. In a solvent-type or active energy line-cured adhesive composition, from the viewpoint of preventing water from being brought into the adhesive composition, in some ways, it is preferred to add compound A in the form of an organic solvent solution that is substantially free of water (for example, the water content relative to 100 parts by weight of compound A is less than 10 parts by weight, less than 5 parts by weight, or less than 1 part by weight). This allows the formation of a more homogeneous pressure-sensitive adhesive layer.

[0155] In some ways, as compound A, from the aspect of being easily well-uniformly matched to the adhesive composition, nonionic compounds are preferably used. According to the adhesive composition well-uniformly matched with compound A, there is a tendency to form an adhesive layer in which compound A is well-uniformly present on the surface. This is to make the adhesive sheet more smoothly peeled off from the adherend, and it is preferred to reduce the load on the adherend due to the change of the peeling force (for example, vibration, impact accompanied by the change).

[0156] The HLB of compound A is not particularly limited. The HLB of compound A may be, for example, 1 or more, or 3 or more. The HLB of compound A is preferably 5 or more, may be 6 or more, may be 8 or more, or may be 9 or more. Thus, there is a tendency to ideally exhibit water-peelable properties. The HLB of compound A is more preferably 10 or more, further preferably 11 or more, further preferably 12 or more, particularly preferably 13 or more, may be 14 or more, may be 15 or more, and may further be 16 or more. By having a compound A with an HLB in the above range, light peeling based on water peeling can be more effectively exhibited. The upper limit of the above HLB is 20 or less, for example, 18 or less. In some embodiments, from the perspective of, for example, compatibility, the HLB of compound A may be 16 or less, for example, 15 or less.

[0157] It should be noted that the HLB in this specification is based on Griffin's Hydrophile-Lipophile Balance, which is a value indicating the degree of affinity of a surfactant for water and oil, and a numerical value between 0 and 20 indicates the ratio of hydrophilicity to lipophilicity. The definition of HLB is as described in WC Griffin: J. Soc. Cosmetic Chemists, 1, 311 (1949), Takahashi Etsutomu, Namba Yoshiro, Koike Motoo, Kobayashi Masao, "Surfactant Handbook", 3rd edition, published by Kogaku Booksha, November 25, 1977, Japan, p179-182, etc. The compound A having the above HLB can be selected based on the technical common sense of a person skilled in the art with reference to the above references, etc. as needed.

[0158] In some embodiments, as compound A, from the viewpoint of affinity with the stripping solution, a compound having two or more hydroxyl groups in one molecule is preferred, and a compound having three or more hydroxyl groups in one molecule is more preferred. As examples of compound A having two or more hydroxyl groups in one molecule, sorbitan monoesters, polyoxyalkylene sorbitan monoesters, polyoxyalkylene glyceryl ethers, polyoxyalkylene diglyceryl ethers, polyoxyalkylene glyceryl ether monoesters, etc. can be cited. The upper limit of the number of hydroxyl groups that compound A has in one molecule is not particularly limited. From the viewpoint of solubility in organic solvents and ease of preparation of adhesive compositions, it is usually appropriate to be less than 10, preferably less than 8, less than 6, or less than 4.

[0159] In some ways, as compound A, from the viewpoint of solubility in organic solvent (for example, esters such as ethyl acetate), it is preferred to select nonionic compounds with fatty acid ester structure.Compound A with fatty acid ester structure also can become advantageous in terms of the compatibility in adhesive layer.For example, as compound A contained in acrylic adhesive layer, it is preferred to adopt compounds with fatty acid ester structure.As the example of nonionic compounds with fatty acid ester structure, sorbitan fatty acid ester, polyoxyalkylene fatty acid ester, polyoxyalkylene fatty acid monoester etc. can be enumerated.

[0160] In some embodiments, compound A is preferably a compound that is liquid at room temperature (here, 25° C.) with a solid content of 100% from the viewpoint of ease of preparation of an organic solvent solution.

[0161] In some embodiments, compound A is preferably a compound that dissolves without phase separation in the following test II, and more preferably a compound that dissolves without phase separation in the following test I. It should be noted that the following tests I and II use compound A in a 100% solid content and are performed at room temperature (23 to 25° C.).

[0162] [Test I]

[0163] 90 g of ethyl acetate and 10 g of compound A were placed in a 200 mL container, stirred with a glass rod for 1 minute, and then left to stand. After 5 minutes, the presence of phase separation was visually observed.

[0164] [Test II]

[0165] 90 g of ethyl acetate and 10 g of compound A were added to a 200 mL container, stirred with a glass rod for 1 minute, treated with an ultrasonic disperser at 35 kHz for 10 minutes, stirred with a glass rod for another 1 minute, allowed to stand, and visually observed for phase separation after 5 minutes.

[0166] As the ultrasonic dispersion device, a device named "ULTRASONIC CLEANER" manufactured by AS ONE or its equivalent can be used.

[0167] The usage amount of compound A is not particularly limited, and can be set in a manner that effectively presents a reduction in the peeling force caused by the supply of the stripping solution. In some ways, the usage amount of compound A can be, for example, about 5 parts by weight or less relative to 100 parts by weight of the base polymer, from the viewpoint of the bonding reliability and water-resistant reliability of the adherend in the stage without the intention of stripping, preferably set to about 3 parts by weight or less, preferably less than 2 parts by weight, more preferably less than 1 part by weight, can be less than 0.8 parts by weight, can be less than 0.6 parts by weight, can be less than 0.4 parts by weight, can be less than 0.2 parts by weight, and can also be less than 0.1 parts by weight. Compound A with high HLB (for example, more than 5, preferably more than 10) has a tendency to easily exert good stripping properties even if added in small amounts. In addition, the amount of compound A relative to 100 parts by weight of the base polymer can be, for example, set to more than 0.001 parts by weight, from the viewpoint of making compound A uniformly well present on the surface of the adhesive layer so that the adhesive sheet is more smoothly stripped from the adherend, it is usually suitable to be set to more than 0.01 parts by weight, preferably more than 0.03 parts by weight (for example, more than 0.1 parts by weight). In a composition in which water-strippability is important, the amount of the compound A may be 0.3 parts by weight or more (eg, 0.5 parts by weight or more) based on 100 parts by weight of the base polymer.

[0168] <Fixed parts>

[0169] The fixing member 2 is, for example, a plate-shaped member, but its shape, structure, etc. are not particularly limited. The fixing member 2 may also be a conductive substrate such as a conductive film, aluminum foil, or a metal vapor-deposited film. The material of the fixing member 2 is also not particularly limited, and the fixing member 2 may be a conductive material or an insulating material. However, in this embodiment, as described later, since the positive electrode for applying a voltage is provided on the fixing member 2, the fixing member 2 is preferably composed of a conductive material, such as a metal. Therefore, there is a case where the fixing member 2 also supports the electrically peelable adhesive layer 1 while passing electricity to the electrically peelable adhesive layer 1.

[0170] <Inspection object>

[0171] In this embodiment, the inspection object of the conductive inspection method includes a conductor 3 and an insulator 4, which is assumed to be a capacitor, but other types of electronic components can also be used as the object. Electronic components that can be the inspection object include capacitors, inductors, chips, resistors, coils, diodes, substrates, switches, etc., but are not particularly limited. In addition, conductive material molded products such as screws that attach importance to conductivity, molded products of conductive treatment materials, molded products of insulating treatment materials, etc. can also be the inspection object of the conductive inspection method. The molded products of conductive treatment materials and the molded products of insulating treatment materials can also include surface treatment materials.

[0172] <Details of the conductivity inspection method>

[0173] First, if Figure 1 As shown on the left side of FIG. 1 , the conductivity inspection method of this embodiment joins a conductor 3 or an insulator 4 as an inspection object to a fixing member 2 using an electrically peelable adhesive layer 1 capable of joining the inspection object to a fixing member 2 .

[0174] Then, if Figure 1 As shown on the left side of FIG. 1 , a voltage is applied to the electro-peelable adhesive layer 1 via the inspection object and the fixing member using a predetermined voltage applying device. The voltage applying device has a positive electrode 5 and a negative electrode 6 for applying voltage, but in this embodiment, the positive electrode 5 is connected to the fixing member 2, and the negative electrode 6 is connected to the conductor 3 or the insulator 4 as the inspection object, respectively. As an example, the electrode is connected to the fixing member 2 and each inspection object via a probe. With such an electrode arrangement, a voltage is applied from the fixing member 2 to the inspection object, and when the inspection object is the conductor 3, the current flows in that direction.

[0175] After voltage is applied, Figure 1 As shown on the right side of the figure, the pass or fail of the inspection object is determined based on the bonding state between the inspection object and the fixing member 2. Specifically, when the inspection object is a conductor 3, since the adhesive force of the electro-peelable adhesive layer 1 is reduced by energization, the inspection object is easily separated from the fixing member 2 and separated under certain conditions. On the other hand, when the inspection object is an insulator 4, no energization is applied, the adhesive force of the electro-peelable adhesive layer 1 is maintained, and the bonding state between the inspection object and the fixing member 2 does not change.

[0176] By observing the change in adhesive force caused by the energization and the change in the bonding state accompanying the change in adhesive force, the tester can determine whether the inspection object is a conductor or an insulator. Therefore, it is possible to easily determine whether the inspection object is a conductor or an insulator without measuring the current value, resistance value, etc. of the inspection object.

[0177] In addition, the present embodiment can also be applied to the inspection of whether the conductor is a qualified product, and the inspection of whether the insulator is a qualified product. When a specified voltage is applied to the conductor, if the conductor is a qualified product, a current above the threshold value flows, so the conductor is easily separated from the fixing component 2, and separation is expected to occur under certain conditions. In the case where a specific conductor does not separate even under such conditions, since the expected current does not flow through the conductor, it can be determined as a defective product. On the other hand, when a specified voltage is applied to the insulator, if the insulator is a good product, the current is zero or only a current less than the threshold value flows, so it is expected that the bonding state between the conductor and the fixing component 2 is maintained. In the case where a specific insulator is separated even under such conditions, since a current not within the expected range flows through the insulator, it can be determined as a defective product.

[0178] That is, the conductivity inspection method of this embodiment can efficiently determine the conductivity characteristics of the inspection object based on the behavior of the inspection object caused by the inspection. In the case where it is unclear whether the inspection object is a conductor or an insulator, the tester can determine whether the inspection object is a conductor or an insulator based on the behavior of the inspection object. In addition, regardless of whether the inspection object is a conductor or an insulator, the tester can determine whether the inspection object is a qualified product or a defective product based on the behavior of the inspection object.

[0179] It should be noted that the number of inspection objects to be inspected at one time may be one, but by inspecting a plurality of inspection objects together, efficient inspection can be performed.

[0180] In addition, the conductive inspection method of this embodiment can also classify the inspection object while determining the conductive characteristics of the inspection object. The classification method is not particularly limited. For example, Figure 2 As shown, by Figure 1 By placing all the components in an upside-down order and applying voltage, only the inspection object separated from the fixing component 2 falls down due to its own weight, so that the fallen inspection object can be classified. By applying voltage, the adhesive force of the electro-peelable adhesive layer 1 to the adherend is reduced, so Figure 2 As shown in FIG. 1 , the inspection object dropped from the electro-peelable adhesive layer 1 after voltage application can be determined to be a conductor 3 or a qualified conductor 3. Figure 2 As shown, the inspection object remaining in the electrically peelable adhesive layer 1 after voltage application can be determined as an insulator 4 or an insulator 4 that is a qualified product. In addition, it is also possible to classify the inspection object by applying an external force such as wind or vibration to the inspection object instead of its own weight, or to press a separately prepared adhesive tape against the inspection object and classify it by whether it can be separated from the electrically peelable adhesive layer 1. In this way, the inspection object can be classified efficiently. Furthermore, for example, by Figure 2 The conductor 3 shown in the figure is dropped on a tray with a shock absorbing material arranged on the bottom, so that the classified inspection objects can be collected without damaging them. Alternatively, the classified inspection objects may be collected by a conveyor belt or the like instead of a tray.

[0181] In this embodiment, the electro-peelable adhesive layer 1 has a single-layer structure, the positive electrode 5 for applying voltage is connected to the fixing member 2, and the negative electrode 6 for applying voltage is connected to the inspection object. Thus, the conductivity inspection method can be implemented with a simple structure.

[0182] <Method for peeling off the inspection object>

[0183] Furthermore, in the conductivity inspection method of the present embodiment, after applying voltage to the inspection object and the electrically peelable adhesive layer 1, a predetermined energy or substance other than electricity may be supplied to the electrically peelable adhesive layer 1. Thus, the conductive properties of the inspection object can be determined, and the remaining inspection object bonded to the electrically peelable adhesive layer 1 after the voltage is applied can be peeled off.

[0184] exist Figure 2 In the example shown, a voltage is applied to the inspection object and the electrically peelable adhesive layer 1, and as a result, the conductor 3 falls off and the insulator 4 is bonded to the electrically peelable adhesive layer 1, and the insulator 4 corresponds to the remaining inspection object. Figure 2 In the state shown in which only the insulator 4 is bonded to the electrically peelable adhesive layer 1, by supplying a predetermined energy or substance other than electricity to the electrically peelable adhesive layer 1, the electrically peelable adhesive layer 1 can be weakened. Figure 3 As shown, after voltage is applied, the insulator 4 bonded to the electrically peelable adhesive layer 1 is peeled off from the electrically peelable adhesive layer 1. Figure 3 In the example shown, the residual inspection object falls from the weakly bonded electrically-peelable adhesive layer 1 due to its own weight, and is peeled off from the electrically-peelable adhesive layer 1. The residual inspection object may be peeled off by applying an external force such as wind or vibration to the inspection object bonded to the electrically-peelable adhesive layer 1 after voltage application, or by pressing the adhesive tape.

[0185] In the case where the electrically strippable adhesive layer 1 is the first embodiment described above, or in the case where the electrically strippable adhesive layer is cured by heating in the second embodiment, the electrically strippable adhesive layer 1 is heated to make the electrically strippable adhesive layer 1 weakly adhesive, and the residual inspection object can be peeled off. In the case where the electrically strippable adhesive layer 1 is cured by irradiation with active energy rays in the second embodiment described above, the electrically strippable adhesive layer 1 is irradiated with active energy rays to make the electrically strippable adhesive layer 1 weakly adhesive, and the residual inspection object can be peeled off. In the case where the electrically strippable adhesive layer 1 is the third embodiment described above, water or alcohol is supplied to the electrically strippable adhesive layer 1 to make the electrically strippable adhesive layer 1 weakly adhesive, and the residual inspection object can be peeled off.

[0186] In the present embodiment, the residual inspection object peeled off from the electro-peelable adhesive layer 1 by supplying a predetermined energy or substance other than electricity can be recovered by a tray, etc. In addition, for example, the inspection object separated from the electro-peelable adhesive layer 1 after voltage application is recovered to the first tray, and the inspection object peeled off from the electro-peelable adhesive layer 1 after supplying a predetermined energy or substance other than electricity is recovered to the second tray, thereby enabling the tester to determine the conductive properties of the inspection object afterwards.

[0187] (Second embodiment)

[0188] <Overview of Conductivity Inspection Method>

[0189] Figure 4 2 is a diagram schematically showing the process of the conductivity inspection method according to the second embodiment of the present invention. The basic content of this embodiment is the same as that of the first embodiment, but an adhesive layer 7 and a conductive layer 8 are further arranged between the electro-peelable adhesive layer 1 and the fixing member 2. When viewed from the fixing member 2 side, the adhesive layer 7, the conductive layer 8, and the electro-peelable adhesive layer 1 are stacked in sequence, and the electro-peelable adhesive sheet 10 obtained by the three layers of the adhesive layer 7, the conductive layer 8, and the electro-peelable adhesive layer 1 can also be arranged between the fixing member 2 and the inspection object (conductor 3 or insulator 4). With the functions of the adhesive layer 7 and the electro-peelable adhesive layer 1, the electro-peelable adhesive sheet 10 can bond the fixing member 2 to the inspection object.

[0190] In this embodiment, the positive electrode 5 for applying voltage is connected to the conductive layer 8, and the negative electrode 6 for applying voltage is connected to the inspection object. Therefore, the fixing member 2 does not necessarily have conductivity, and mainly plays a role of supporting the electrically peelable adhesive sheet 10. In addition, since the electrically peelable adhesive sheet 10 is provided with a notch portion 12 formed by removing a part of the electrically peelable adhesive layer 1, especially the edge portion, the positive electrode 5 and the conductive layer 8 can be easily electrically connected by, for example, bringing a probe into contact with the notch portion 12.

[0191] <Adhesive Layer>

[0192] The adhesive layer 7 contains a polymer for imparting adhesiveness to the adhesive layer 7. As the adhesive layer 7, the adhesive layer described as the "adhesive layer" in the first embodiment can be used as it is.

[0193] <Conductive Layer>

[0194] The conductive layer 8 is not particularly limited as long as it has a conductive layer, and the conductive layer described as the "conductive layer" in the first embodiment can be used as it is. Figure 4 As shown, the conductive layer 8 may be a single-layer structure, or may be used in the form of a laminated structure having a conductive layer and a substrate (a substrate for conducting electricity). As a substrate for conducting electricity having a laminated structure having a conductive layer and a substrate, the substrate described as the "substrate for conducting electricity" in the first embodiment may be used directly.

[0195] <Details of the conductivity inspection method and the peeling method>

[0196] First, if Figure 4 As shown on the left side of FIG. 1 , the conductivity inspection method of this embodiment joins the conductor 3 or the insulator 4 as the inspection object to the fixing member 2 using the electrically-peelable pressure-sensitive adhesive sheet 10 capable of joining the inspection object to the fixing member 2 .

[0197] Then, if Figure 4 As shown on the left side of , a voltage is applied to the inspection object and the electrically peelable adhesive layer 1 of the electrically peelable adhesive sheet 10 using a predetermined voltage applying device. In the present embodiment, the voltage is applied to the electrically peelable adhesive layer 1 via the inspection object and the conductive layer 8 of the electrically peelable adhesive sheet 10. The voltage applying device has a positive electrode 5 and a negative electrode 6 for applying voltage, but in the present embodiment, the positive electrode 5 is connected to the conductive layer 8 of the electrically peelable adhesive sheet 10, and the negative electrode 6 is connected to the conductor 3 or the insulator 4 as the inspection object. As an example, the electrode is connected to the conductive layer 8 and each inspection object via a probe. By such an electrode arrangement, a voltage is applied from the conductive layer 8 to the inspection object, and when the inspection object is the conductor 3, the current flows in this direction.

[0198] After the voltage is applied, the pass / fail of the inspection object is determined according to the bonding state between the inspection object and the fixing member 2. The subsequent determination is the same as that of the first embodiment.

[0199] In this embodiment, a three-layered electrically peelable adhesive sheet 10 is used, which includes an adhesive layer 7 and a conductive layer 8 in addition to the electrically peelable adhesive layer 1. This allows the conductivity inspection method to be performed while the inspection object is securely bonded to the fixing member 2. In addition, an insulator can be used as the fixing member 2.

[0200] In addition, in this embodiment, after applying voltage to the inspection object and the electrically peelable adhesive layer 1 of the electrically peelable adhesive sheet 10, a predetermined energy or substance other than electricity may be supplied to the electrically peelable adhesive layer 1, similarly to the first embodiment. Thus, the conductive properties of the inspection object can be determined, and the residual inspection object in the inspection object that is bonded to the electrically peelable adhesive layer 1 after the voltage is applied can be peeled off. Furthermore, the peeled residual inspection object can be recovered.

[0201] It should be noted that the present invention is not limited to the above-mentioned embodiments, and can be appropriately deformed, improved, etc. In addition, the material, shape, size, value, form, quantity, configuration position, etc. of each component in the above-mentioned embodiments are arbitrary and not limited as long as they can realize the present invention.

[0202] (Supplementary explanation)

[0203] Here, the features of the above-mentioned conductive inspection method, peeling method, electro-peelable adhesive layer, and adhesive sheet according to the embodiments of the present invention are briefly summarized in the following [1] to

[20] .

[0204] [1] A method for conducting an electrical conductivity test, wherein an object to be tested is bonded to a fixing member using an electrically peelable adhesive layer capable of bonding the object to be tested to the fixing member,

[0205] applying a voltage to the inspection object and the electro-peelable adhesive layer,

[0206] The conductive property of the inspection object is determined based on the bonding state between the inspection object and the fixing member after voltage application.

[0207] [2] The conductivity inspection method according to [1] above, wherein whether the inspection object is a conductor or an insulator is determined based on the conductivity characteristics of the inspection object.

[0208] [3] The conductivity inspection method according to [1] above, wherein whether the inspection object is a conforming product or a defective product is determined based on the conductivity characteristics of the inspection object.

[0209] [4] The conductivity inspection method according to any one of [1] to [3] above, wherein the inspection object is classified simultaneously with the determination of the conductivity characteristics of the inspection object.

[0210] [5] The conductivity inspection method according to any one of [1] to [4] above, wherein the fixing member has conductivity,

[0211] A voltage is applied to the electrically peelable adhesive layer via the inspection object and the fixing member.

[0212] [6] The conductivity inspection method according to any one of [1] to [5] above, wherein the electrically peelable adhesive layer has a single-layer structure,

[0213] The fixing member has electrical conductivity,

[0214] A positive electrode for applying a voltage is connected to the fixing member, and a negative electrode for applying a voltage is connected to the inspection object.

[0215] [7] A conductivity inspection method according to any one of [1] to [6] above, wherein a voltage is applied to the electrically peelable adhesive layer via the inspection object and the conductive layer in a state where an adhesive layer and a conductive layer are further arranged between the electrically peelable adhesive layer and the fixing member.

[0216] [8] The conductivity inspection method according to [7] above, wherein a positive electrode for applying a voltage is connected to the conductive layer, and a negative electrode for applying a voltage is connected to the inspection object.

[0217] [9] The conductivity inspection method according to any one of [1] to [8] above, wherein the electro-peelable adhesive layer contains an electrolyte.

[0218]

[10] The conductivity inspection method according to any one of [1] to [9] above, wherein the electro-peelable adhesive layer contains an ionic liquid.

[0219]

[11] The conductivity inspection method according to

[10] above, wherein the anion of the ionic liquid is selected from (FSO 2 ) 2 N - ,(CF 3 SO 2 ) 2 N - ,(CF 3 CF 2 SO 2 ) 2 N - ,(CF 3 SO 2 ) 3 C - , CH 3 COO - CF 3 COO - CF 3 CF 2 CF 2 COO - CF 3 SO 3- CF 3 (CF 2 ) 3 SO 3 - Br - 、AlCl 4 - 、Al 2 Cl 7 - 、NO 3 - , BF 4 - PF 6 - , AsF 6 - , SbF 6 - , and F(HF) n - (n represents an integer greater than or equal to 1) at least one anion selected from the group consisting of:

[0220]

[12] A peeling method, wherein in the conductivity inspection method described in any one of [1] to

[11] above,

[0221] After applying voltage to the inspection object and the electro-peelable adhesive layer,

[0222] supplying a predetermined energy or substance other than electricity to the electro-peelable adhesive layer,

[0223] The conductive property of the inspection object is determined, and the remaining inspection object bonded to the electrically peelable adhesive layer after the voltage is applied is peeled off.

[0224]

[13] The stripping method according to

[12] above, wherein the residual inspection object is an insulator.

[0225]

[14] The peeling method according to

[12] or

[13] above, wherein heat is supplied to the electro-peelable adhesive layer as the predetermined energy.

[0226]

[15] The peeling method according to

[12] or

[13] above, wherein active energy rays are supplied to the electro-peelable adhesive layer as the predetermined energy.

[0227]

[16] The peeling method according to any one of

[12] to

[15] above, wherein:

[0228] After applying voltage to the inspection object and the electro-peelable adhesive layer,

[0229] The conductive properties of the inspection object are determined, and then,

[0230] supplying a predetermined energy or substance other than electricity to the electro-peelable adhesive layer,

[0231] The remaining inspection object is peeled off.

[0232]

[17] An electro-strippable adhesive layer comprising: a polymer; an electrolyte; and a thermally expandable filler.

[0233]

[18] An electro-peelable adhesive layer comprising a polymer and an electrolyte, the electro-peelable adhesive layer being cured by irradiation of active energy rays or by heating.

[0234]

[19] An electro-peelable adhesive layer comprising: a polymer; an electrolyte; and at least one compound selected from the group consisting of a surfactant and a compound having a polyoxyalkylene skeleton.

[0235]

[20] A pressure-sensitive adhesive sheet comprising the electro-peelable pressure-sensitive adhesive layer according to any one of

[17] to

[19] above.

[0236] Example

[0237] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0238] [Examples 1-2, Comparative Example 1]

[0239] <Polymer>

[0240] (Preparation of Acrylic Polymer 1 Solution)

[0241] 87 parts by mass of n-butyl acrylate (BA) as monomer components, 10 parts by mass of 2-methoxyethyl acrylate (MEA), 3 parts by mass of acrylic acid (AA) and 150 parts by mass of ethyl acetate as a polymerization solvent were placed in a removable flask and stirred for 1 hour while introducing nitrogen. After removing oxygen from the polymerization system, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) was added as a polymerization initiator, and the temperature was raised to 63°C and reacted for 6 hours. Then, ethyl acetate was added to obtain an acrylic polymer 1 solution with a solid content concentration of 40% by mass. The weight average molecular weight of the obtained acrylic polymer 1 was 750,000.

[0242] <Preparation of Adhesive Composition>

[0243] As shown in Table 1, the acrylic polymer solution obtained above, the ethyl acetate solution of each tackifier adjusted to 50% by weight, the crosslinking agent, the ionic liquid, and the heat-expandable filler components shown below were stirred and mixed to obtain the adhesive compositions (solutions) for electrical stripping of Examples 1 to 2 and Comparative Example 1 adjusted to 25% by weight. It should be noted that ethyl acetate was used to adjust the solid content concentration of the adhesive composition. Table 1 shows the blending amount of each component.

[0244] In addition, the value of each component in Table 1 is a mass part. In addition, the compounding amount (mass part) of a polymer and a tackifier each shows the compounding amount (mass part) calculated as a solid content.

[0245] <Production of Electro-Releasable Adhesive Layer>

[0246] The above-obtained electro-peelable adhesive composition (solution) was applied to the release-treated surface of a polyethylene terephthalate release liner (trade name "MRF38", manufactured by Mitsubishi Chemical Corporation) with a uniform thickness using an applicator. Next, heat drying was performed at 80°C for 5 minutes, and the release-treated surface of the polyethylene terephthalate release liner (trade name "MRE38", manufactured by Mitsubishi Chemical Corporation) was laminated on the adhesive layer using a hand roller. Then, heating was performed at 50°C for 48 hours to obtain an electro-peelable adhesive layer with a thickness of 60 μm.

[0247] <Preparation of Single-Sided PSA Sheet with Substrate>

[0248] The obtained electrically removable adhesive layer was formed into a sheet with a size of 10 mm × 80 mm, the release liner (MRE38) was peeled off, and the metal layer side of a film with a metal layer (trade name "1005CR", manufactured by Toray Industries, Ltd., thickness 12 μm, size 10 mm × 100 mm) was adhered to the exposed electrically removable adhesive layer to prepare a single-sided adhesive sheet with a substrate.

[0249] <Production of Joint>

[0250] The release liner (MRF38) of the single-sided adhesive sheet with a substrate was peeled off, and a stainless steel plate as an adherend was attached to the peeled surface so that one end of the adhesive sheet protruded about 2 mm from the adherend. The adhesive was pressed back and forth once with a 2 kg roller, and left to stand at 23° C. for 30 minutes to obtain a bonded body including a stainless steel plate 6 / electrically peelable adhesive layer 1′ / film with a metal layer (electrically conductive substrate) 5′. The outline of the bonded body is shown in FIG. Figure 5 .

[0251] <Evaluation>

[0252] (Usually peel strength)

[0253] The bonded bodies of the examples and comparative examples were used to perform a 180° peel strength test. The adherend used was a stainless steel plate (SUS304, size: 30 mm×120 mm).

[0254] The peel tester (trade name "variable angle peel tester YSP", manufactured by Asahi Seiko Co., Ltd.) was used to test the Figure 5 The film was peeled off in the direction of the arrow in the figure, and the adhesive strength in a 180° peel test (tensile speed: 300 mm / min, peeling temperature 23° C.) was measured, and the 180° peel force was taken as the normal peel force.

[0255] The measurement results are shown in Table 1. The unit of the normal peel force shown in Table 1 is N / cm.

[0256] (Electro-peel force)

[0257] A stainless steel plate (SUS304, size: 30 mm × 120 mm) was used as the adherend. The bonded body was pressed back and forth once with a 2 kg roller to prepare the bonded body. After being placed in an environment of 23°C for 30 minutes, the bonded body was peeled off. Figure 5 The negative and positive electrodes of a DC current machine are installed at the α and β positions respectively, and a voltage of 30 V is applied for 30 seconds. Immediately after the application is stopped, peeling is performed in the same manner as the above-mentioned normal peeling force measurement, and the adhesive force during the voltage application is measured as the electrical peeling force.

[0258] In addition, the case where the electric peel force was 0.5 N / cm or less was evaluated as ○, and the case where the electric peel force exceeded 0.5 N / cm was evaluated as ×. The measurement results are shown in Table 1.

[0259] (Thermal peel strength)

[0260] A stainless steel plate (SUS304, size: 30 mm × 120 mm) was used as the adherend. The bonded body was pressed back and forth once with a 2 kg roller to prepare the bonded body. After being placed in an environment of 23°C for 30 minutes, the stainless steel plate side before peeling was heated at 150°C for 60 seconds using a thermal stirrer. Immediately thereafter, peeling was performed in the same manner as the above-mentioned normal peeling strength measurement, and the adhesive strength was measured as the thermal peeling strength.

[0261] In addition, the case where the heat peeling force was 0.5 N / cm or less was evaluated as ○, and the case where it exceeded 0.5 N / cm was evaluated as ×. The measurement results are shown in Table 1.

[0262] (Production of drop test specimen)

[0263] The adhesive obtained above was pasted on a stainless steel plate (SUS304, size: 30mm×120mm). A conductor and an insulator were adhered to the adhesive and used as a drop test body. A 100g stainless steel sheet (SUS304) was used as the conductor, and a 100g resin sheet was used as the insulator. The bonding area between the stainless steel sheet and the adhesive layer and the bonding area between the resin sheet and the adhesive were 10mm 2 .

[0264] (Drop test)

[0265] The drop test body sample is held in such a way that the bonding surface of the conductor and the insulator is the lower surface (see Figure 2 ).

[0266] The positive electrode of the DC current machine was attached to the stainless steel plate, and the negative electrode of the DC current machine was attached to the conductor and the insulator, and a voltage of 30 V was applied for 30 seconds.

[0267] Next, the drop test body sample was held in a 150° C. environment for 60 seconds so that the bonding surface between the conductor and the insulator was on the lower side.

[0268] The case where only the conductor fell when the voltage was applied and the insulator fell when heated at 150°C was evaluated as ○, the case where only the conductor fell when the voltage was applied and the insulator did not fall when heated at 150°C was evaluated as △, and the other cases were evaluated as ×.

[0269] [Table 1]

[0270] Table 1

[0271]

[0272] The details of the raw materials in Table 1 are as follows.

[0273] (Ionic Liquid)AS-110

[0274] Cation: 1-ethyl-3-methylimidazolium cation, anion: bis(fluorosulfonyl)imide anion, trade name "ELEXCEL AS-110", manufactured by Daiichi Kogyo Seiyaku Co., Ltd.

[0275] (Thermal expansion filler) FN-100SD

[0276] Average particle size: 10-20 μm, expansion start temperature: 125-135°C

[0277] Trade name: "Matsumoto Microsphere FN-100SD" manufactured by Matsumoto Oil & Fats Pharmaceutical Co., Ltd.

[0278] (Crosslinker)TETRAD C

[0279] Epoxy crosslinking agent, trade name "TETRAD-C" manufactured by Mitsubishi Gas Chemical Co., Ltd.

[0280] In the peeling test using the electrically stripping adhesive layer of Example 1 and Example 2, the electrical stripping force was less than 0.5 N / cm, which was good, and in the drop test, only the conductor fell when the voltage was applied. Therefore, it was verified that when the electrically stripping adhesive layer of Examples 1 and 2 was used, it can be applied to determine the conductive characteristics of the inspection object, and at the same time, the inspection object can also be classified. In addition, in the drop test using the electrically stripping adhesive layer of Example 1, it was verified that the insulator bonded to the electrically stripping adhesive fell when heated at 150°C after the voltage was applied. On the other hand, in the peeling test using the electrically stripping adhesive of Comparative Example 1, the electrical stripping force was 1.5 N / cm, and no decrease was found compared to the normal stripping force, and the conductor did not fall when the voltage was applied in the drop test.

[0281] It should be noted that the present application is based on the Japanese patent application (Japanese Patent Application No. 2022-125642) filed on August 5, 2022, and the contents thereof are incorporated herein by reference.

[0282] Description of Reference Numerals

[0283] 1 Electro-stripping adhesive layer

[0284] 2 Fixing parts

[0285] 3 Conductors (objects to be inspected)

[0286] 4 Insulator (object to be inspected)

[0287] 7 Adhesive layer

[0288] 8 Conductive layer

[0289] 10 Electrically peelable adhesive sheet

[0290] 12 Notch

Claims

1. Conductive inspection method, wherein: The inspection object is bonded to the fixing member using an electrically peelable adhesive layer capable of bonding the inspection object to the fixing member, applying a voltage to the inspection object and the electro-peelable adhesive layer, The conductive property of the inspection object is determined based on the bonding state between the inspection object and the fixing member after voltage application.

2. The conductivity inspection method according to claim 1, wherein: Based on the conductive characteristics of the inspection object, it is determined whether the inspection object is a conductor or an insulator.

3. The conductivity inspection method according to claim 1, wherein: Based on the conductive characteristics of the inspection object, it is determined whether the inspection object is a conforming product or a defective product.

4. The conductivity inspection method according to claim 1, wherein: The inspection object is classified simultaneously with the determination of the conductive property of the inspection object.

5. The conductivity inspection method according to claim 1, wherein: The fixing member has electrical conductivity, A voltage is applied to the electrically peelable adhesive layer via the inspection object and the fixing member.

6. The conductivity inspection method according to claim 1, wherein: The electro-peelable adhesive layer has a single-layer structure, The fixing member has electrical conductivity, A positive electrode for applying a voltage is connected to the fixing member, and a negative electrode for applying a voltage is connected to the inspection object.

7. The conductivity inspection method according to claim 1, wherein: A voltage is applied to the electrically-debonding adhesive layer via the inspection object and the conductive layer in a state where an adhesive layer and a conductive layer are further arranged between the electrically-debonding adhesive layer and the fixing member.

8. The conductivity inspection method according to claim 7, wherein: A positive electrode for applying a voltage is connected to the conductive layer, and a negative electrode for applying a voltage is connected to the inspection object.

9. The conductivity inspection method according to claim 1, wherein: The electro-strippable adhesive layer includes an electrolyte.

10. The conductivity inspection method according to claim 9, wherein: The electro-release adhesive layer comprises an ionic liquid.

11. The conductivity inspection method according to claim 10, wherein: The anion of the ionic liquid is selected from (FSO2)2N - 、(CF3SO2)2N - 、(CF3CF2SO2)2N - 、(CF3SO2)3C - 、CH3COO - CF3COO - CF3CF2CF2COO - CF3SO3 - CF3(CF2)3SO3 - Br - 、AlCl4 - 、Al2Cl7 - 、NO3 - 、BF4 - PF6 - 、AsF6 - 、SbF6 - , and F(HF) n - (n represents an integer greater than or equal to 1) at least one anion selected from the group consisting of:

12. A stripping method, wherein: In the conductivity inspection method according to any one of claims 1 to 11, After applying voltage to the inspection object and the electro-peelable adhesive layer, supplying a predetermined energy or substance other than electricity to the electro-peelable adhesive layer, The conductive property of the inspection object is determined, and the remaining inspection object bonded to the electrically peelable adhesive layer after the voltage is applied is peeled off.

13. The stripping method according to claim 12, wherein: The residue inspection object is an insulator.

14. The stripping method according to claim 12, wherein: Heat is supplied to the electro-peelable adhesive layer as the predetermined energy.

15. The stripping method according to claim 12, wherein: Active energy rays are supplied to the electro-peelable adhesive layer as the predetermined energy.

16. The stripping method according to claim 12, wherein: After applying voltage to the inspection object and the electro-peelable adhesive layer, The conductive properties of the inspection object are determined, and then, supplying a predetermined energy or substance other than electricity to the electro-peelable adhesive layer, The remaining inspection object is peeled off.

17. An electro-strippable adhesive layer comprising: a polymer; an electrolyte; and a thermally expandable filler.

18. An electro-peelable adhesive layer comprising a polymer and an electrolyte, the electro-peelable adhesive layer being cured by irradiation of active energy rays or by heating.

19. An electro-detachable adhesive layer comprising: a polymer; an electrolyte; and at least one compound selected from the group consisting of a surfactant and a compound having a polyoxyalkylene skeleton. 20 . A pressure-sensitive adhesive sheet comprising the electro-peelable pressure-sensitive adhesive layer according to claim 17 .

Citation Information

Patent Citations

  • Method for manufacturing electric double layer capacitor and inspection method of electric double layer capacitor

    JP2018041821A

  • Method for manufacturing electric double layer capacitor and inspection method of electric double layer capacitor

    JP2018041822A

  • Adhesive sheet and use thereof

    JP2020125436A

  • Earthquake-resistant notched brick

    JP2022125642A